Pengaruh Fitur Shopee Paylater, Perilaku Impulse Buying Dan Motivasi Hedonis Terhadap Sikap Tabzir Pada Mahasiswa Ekonomi Syariah UIN Fatmawati Sukarno Bengkulu - Yudia Gusti Fitiyani; Supardi Mursalin; Rahmat Putra Ahmad Hasibuan (CV. ITTC INDONESIA, 2026)
This study aims to determine the effect of the Shopee PayLater feature, impulse buying behavior and hedonic motivation on tabzir attitudes in Islamic economics students of UIN Fatmawati Sukarno Bengkulu. This study uses a quantitative method that uses multiple linear regression with primary data collection techniques in the form of questionnaires distributed to 168 respondents. The results of this study reveal that: (1) the Shopee PayLater feature does not affect tabzir attitudes in Islamic economics students (2) impulse buying behavior affects tabzir attitudes in Islamic economics students (3) hedonic motivation affects tabzir attitudes in Islamic economics students (4) the Shopee PayLater feature, impulse buying behavior and hedonic motivation together influence tabzir attitudes in UIN Fatmawati Sukarno Bengkulu students. These findings provide insights into the importance of managing consumer behavior among students to prevent wasteful spending, particularly regarding the use of online payment features that facilitate excessive consumption.